2021
DOI: 10.1155/2021/5843816
|View full text |Cite
|
Sign up to set email alerts
|

Satellite and Scene Image Classification Based on Transfer Learning and Fine Tuning of ResNet50

Abstract: Image classification has gained lot of attention due to its application in different computer vision tasks such as remote sensing, scene analysis, surveillance, object detection, and image retrieval. The primary goal of image classification is to assign the class labels to images according to the image contents. The applications of image classification and image analysis in remote sensing are important as they are used in various applied domains such as military and civil fields. Earlier approaches for remote … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 63 publications
0
28
0
Order By: Relevance
“…The authors proposed the layers of a CNN model to fit a residual mapping instead of stacking each layer directly. Since it was introduced in 2015, ResNet was used in many classification tasks [ 26 , 27 ]. In healthcare, ResNet has been used with success in tasks such as pneumonia detection in chest Xray images [ 28 ], knee anterior cruciate ligament detection [ 29 ], breast cancer detection [ 30 ].…”
Section: Proposed Methodsmentioning
confidence: 99%
“…The authors proposed the layers of a CNN model to fit a residual mapping instead of stacking each layer directly. Since it was introduced in 2015, ResNet was used in many classification tasks [ 26 , 27 ]. In healthcare, ResNet has been used with success in tasks such as pneumonia detection in chest Xray images [ 28 ], knee anterior cruciate ligament detection [ 29 ], breast cancer detection [ 30 ].…”
Section: Proposed Methodsmentioning
confidence: 99%
“…The rest of the parameters include random seed number of 1, and stochastic gradient descendent ( sgd ) as a network optimiser because of its rapid convergence and fast training speed. We used the default value for most of the other learning parameters, such as momentum rate of 0.9 and learn rate factor 0.1, because previous research in [36] has established that they do not affect the performance of a network, whereas others [37, 38] showed that these default values produced reasonable results. The model performance was concurrently validated during the training process using a validation frequency of five (instead of default value 50) to reduce the computing time.…”
Section: Methodsmentioning
confidence: 99%
“…It has 20 classes in it. Training and testing ratio for SAT datasets is selected as 80:20, respectively, whereas for UCMD, it is 70:30 [65,66]. Figure 4 shows the basic process of image classification for CNN.…”
Section: Convolutional Neural Networkmentioning
confidence: 99%
“…e description such as image size, total number of images, images per class, and date of creation is referred to [65]. ere are a total of 21 distinctive scene categories with 100 images per class and dimensions of 256 × 256 pixels, as shown in dataset description table.…”
Section: Uc Merced Land Usementioning
confidence: 99%
See 1 more Smart Citation